ANALISIS PENGARUH PERUBAHAN PEMBEBANAN NON-LINEAR TERHADAP KINERJA GENERATOR ALTERNATING CURRENT (AC) TIGA FASA - Nurbaya Harun Baya; Titi Andriani; Indra Darmawan; Masyitah Aulia (Program Studi Teknik Elektro, 2023)
used quantitative methods, namely, analytical, experimental methods where researchers used a software PSIM where the loads used are three-phase capacitors, three-phase RC loads, three-phase RL loads and three-phase RLC loads, so that the lowest efficiency results are obtained at three-phase capacitor loads, namely 40%, and the highest efficiency is 98%. , at three-phase RC load the highest efficiency is 95% and the lowest efficiency is 54%, at three-phase RL load the highest efficiency is 92% and the lowest is 30%, while at three-phase RLC load the highest efficiency is 94% and the lowest is 49 %. This efficiency can show that the performance of the generator can produce energy in accordance with its efficiency from the total energy used so that it does not convert into heat in a system or circuit. Where for the voltage THD on the three-phase capacitor load the highest is 23% and the lowest is 4%, while the highest current THD is 12% and the lowest is 1%, on a three-phase RC load with the highest voltage THD is 18% and the lowest is 1 %, while the highest current THD is 9% and the lowest is 1%, for a three-phase RL load with the highest voltage THD is 12% and the lowest is 1%, while the highest current THD is 7% and the lowest is 1%, and for RLC three-phase with the highest voltage THD of 18% and the lowest of 1%, while the highest current THD is 12% and the lowest is 1%.